A new immunosuppressive pregnane glycoside from aqueous fraction of Epigynum cochinchinensis - Zong Wan; Yuan-Cheng Yao; Fei Gao; Sheng-Bao Cai; Afsar Khan; Tian-Rui Zhao; Xiao-Yan Yang; Jian Fan; Sheng-Yan Qian; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Pollution characteristics and ecological risk assessment of HCHs and DDTs in estuary wetland sediments from the Bohai Bay, North China - Qing Liu; Shengyan Tian; Rui Jia; Xianbin Liu (Environmental Science and Pollution Research, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Comparative study of the leaf transcriptomes and ionoms of Juglans regia and its wild relative species Juglans cathayensis - Zhongcheng Zhou; Muxian Han; Mei Hou; Xiaojing Deng; Rui Tian; Shuifa Min; Jinbo Zhang (Acta Physiologiae Plantarum, 2017)

Spatiotemporal Variability of Contaminants in Lake Water and Their Risks to Human Health: A Case Study of the Shahu Lake Tourist Area, Northwest China - Peiyue Li; Wei Feng; Chenyang Xue; Rui Tian; Siting Wang (Exposure and Health, 2017)

Molecular Mechanisms of Vascular Dementia: What Can Be Learned from Animal Models of Chronic Cerebral Hypoperfusion? - Si-Qi Du; Xue-Rui Wang; Ling-Yong Xiao; Jian-Feng Tu; Wen Zhu; Tian He; Cun-Zhi Liu (Molecular Neurobiology, 2017)

Remains of trilobites and other species discovered in a volcanic ash bed of the end-Permian, Yangtze craton, South China - Zejin Shi; Leixun Lu; Guan Yin; Hongyu Long; Wenjie Li; Huaixin Yang; Rui Cao; Xuesong Tian; Qian Tan; Kun Wang; Yong Wang; Yaming Tian (International Geology Review, 2017)

Seco-pregnane glycosides from the stems of Epigynum auritum - Fei Gao; Yuan-Cheng Yao; Zong Wan; Sheng-Bao Cai; Jian Fan; Tian-Rui Zhao; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

Progress, opportunities, and key fields for groundwater quality research under the impacts of human activities in China with a special focus on western China - Peiyue Li; Rui Tian; Chenyang Xue; Jianhua Wu (Environmental Science and Pollution Research, 2017)

Characterization of uncultivated magnetotactic bacteria from the sediments of Yuehu Lake, China - Haijian Du; Rui Zhang; Wenyan Zhang; Cong Xu; Yiran Chen; Hongmiao Pan; Ke Zhou; Long-fei Wu; Tian Xiao (Acta Oceanologica Sinica, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

A new C 20 -diterpenoid alkaloid from the lateral roots of Aconitum carmichaeli - Jing Yu; Tian-Peng Yin; Jia-Peng Wang; Rui-Feng Mei; Le Cai; Zhong-Tao Ding (Natural Product Research, 2017)

Nurr1 promotes intestinal regeneration after ischemia/reperfusion injury by inhibiting the expression of p21 (Waf1/Cip1) - Guo Zu; Jihong Yao; Anlong Ji; Shili Ning; Fuwen Luo; Zhenlu Li; Dongcheng Feng; Yiqi Rui; Yang Li; Guangzhi Wang; Xiaofeng Tian (Journal of Molecular Medicine, 2017)